Jawabanmu

Jawaban paling cerdas!
2014-05-04T17:24:24+07:00
X² - 2x - 4 = 0 didapat a= 1 , b = -2 dan c = -4
x1² + x2² = (x1 + x2)² - 2x1x2
               = (-b/a)² - 2c/a
               = 4 + 8
               = 12

x1³ + x2³ = (x1 + x2)³ - 3x1x2(x1 + x2)
               = 4³ - 3(-4)(2)
               = 64 +24
               = 88

x1² + x1²x2 + x1x2² + x2² = (x1² + x2²) + x1x2(x1 + x2)
                                         =  12 + (-4)(-2)
                                         = 12 + 8
                                         = 20
1/(x1 - 3) + 1/(x2 - 3) = x2 - 3 + x1 - 3
                                     (x1 - 3)(x2 - 3)
                                 = x1 + x2 - 6
                                   x1x2 -3(x1+x2) + 9
                                =       -2 - 6
                                   -4 -3(-2)+9
                                 = -8/11

 

2 5 2